2014
DOI: 10.1073/pnas.1316728111
|View full text |Cite
|
Sign up to set email alerts
|

Interepithelial signaling with nephric duct is required for the formation of overlying coelomic epithelial cell sheet

Abstract: In most organs of the body, epithelial tissues are supported by their own basement membrane and underlying stroma, the latter being regarded as a complex of amorphous cells, extracellular matrices, and soluble factors. We demonstrate here that an epithelial tube can serve as a component of stroma that supports the formation of epithelial cell sheet derived from a different origin. During development of the mesonephros in chicken embryos, the intermediate mesoderm (IMM), which contains the Wolffian duct (WD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…However, recent in vivo studies suggest that in addition to paracrine functions (Yoshino et al, 2014), Fn1 could also signal in a cell-autonomous manner (Cseh et al, 2010;Liu et al, 2010;Serres et al, 2014;Stenzel et al, 2011). By using genetic and cell biological approaches, the studies reported in this paper are the first to demonstrate the requisite, cell-autonomous role of Fn1 in the regulation of cardiovascular development.…”
Section: Role Of Fn1 and Integrin α5 In Nc Development And Cardiovascmentioning
confidence: 80%
“…However, recent in vivo studies suggest that in addition to paracrine functions (Yoshino et al, 2014), Fn1 could also signal in a cell-autonomous manner (Cseh et al, 2010;Liu et al, 2010;Serres et al, 2014;Stenzel et al, 2011). By using genetic and cell biological approaches, the studies reported in this paper are the first to demonstrate the requisite, cell-autonomous role of Fn1 in the regulation of cardiovascular development.…”
Section: Role Of Fn1 and Integrin α5 In Nc Development And Cardiovascmentioning
confidence: 80%
“…Interplay between the WD and the CE has also been reported in the nephric region at more posterior levels (18th-22nd somites) (Yoshino et al, 2014). In this report, the authors showed that in the absence of the WD, the overlying CE fails to undergo proper epithelialization, and also that these WD-CE interactions are mediated by fibronectin produced by the WD.…”
Section: Participation Of Wd-derived Signals In MD Specificationmentioning
confidence: 53%
“…Other possibilities include cell-cell contacts, instead of soluble factors, considering the close proximity between the Müllerian and Wolffian ducts. Indeed, a role of fibronectin in Wolffian duct formation was reported in chick embryos (Yoshino et al, 2014). According to the GUDMAP database, integrin b7 is expressed in the Müllerian duct, while nephronectin is expressed in the Wolffian duct.…”
Section: Discussionmentioning
confidence: 99%